Estratégias de aprendizagem efetivas no ensino médio segundo os professores por áreas do conhecimento - Nascimento, Katiane Santos dos (2021)
The present research has the objective to identify and analyze the learning strategies for High School pointed out by teachers as being effective considering the cognitive and meta cognitive character, by area of knowledge. It comprises applied research, of quality-quantitative approach, of descriptive and exploratory character. The data was collected from teachers in High School from three public schools and three private schools from the State Education network in Foz do Iguassu City, Paraná, Brazil. We used adapted instrument from the Scale of Learning Strategies Assessment for Basic Education (EAVAP-EF). We analyzed the data through descriptive statistics, comparing the highest percentages of teachers’ indications of their strategies applied to public schools to those applied to private schools and viceversa. As a result of this study, we identified that in the Languages field, among the strategies teachers pointed out as being effective, the meta cognitive strategies overlap; in the human sciences and math fields, the indications of cognitive strategies overlap; and in the nature sci ence field there was practically a draw between the cognitive and the meta cognitive strategies. We have concluded that, in High School, in the sample we studied, teachers value the cognitive strategies as much as the self-regulatory ones. We can also conclude that there need to be advances in research and productions concerning this theme, not only in teachers’ graduation so that they can learn how to teach students to be self-regulated but also in the areas of knowledge field.